Reflection‐refraction effects on light distribution inside tubular photobioreactors. (13th March 2017) - Marotta, Gaspare; Pruvost, Jeremy; Scargiali, Francesca; Caputo, Giuseppe; Brucato, Alberto
Abstract : One of the main parameters affecting autotrophic algae cultures is photon absorption distribution inside the photobioreactor. This clearly depends on the geometry of both the radiation source and the photobioreactor, as well as on algae suspension optical properties. In this work the local volumetric rate of photon absorption LVRPA in a cross‐section of a horizontal‐pipe photobioreactor was investigated by means of simplified Monte Carlo simulations. In particular, the fate of a number of photons perpendicularly hitting the photobioreactor circular section was simulated in relation to different values of algae concentration. The model takes into account refraction/reflection phenomena at the air/photobioreactor‐wall interface. Simulation results show that radiation distribution inside the photobioreactor is quite strongly affected by reflection/refraction at the air‐reactor interface. In particular, dark zones (not revealed when neglecting reflection/refraction phenomena) are observed in conjunction with unexpected radiation intensification in other zones. These phenomena are bound to affect photobioreactor performance and should therefore be considered if effective photobioreactor models are sought.